MODEL PENGEMBANGAN ASET WAKAF PROVINSI JAWA TENGAH SEBAGAI SUPPORT SYSTEM EKONOMI RUMAH TANGGA PETANI BAWANG MERAH - Khaerunisa Azkia; Tuti Kurnia; Wildan Munawar (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to determine the management of waqf assets in Central Java and the development model of waqf assets in Central Java as an economic support system for shallot farmer households. The research method uses descriptive qualitative research with quantitative approach, data analysis techniques used Analytical Network Process, data collection through interviews and distributing questionnaires. The results showed that Central Java province has waqf assets totaling 112,834 locations. The management of waqf assets in Central Java is used for the construction of 76,817 mosques, 31,414 educational waqf, health waqf and vacant land waqf as many as 23 locations. The priority needs of farmers are improving marketing, providing marketing places, providing storage warehouses, subsidizing pesticides and providing shallot dryers (double blowers). Based on this, the appropriate waqf model to help the needs of farmers is the utilization of vacant waqf land for the provision of shallot storage warehouses called the Shallot Storage model (PBM), and the utilization of pesantren waqf land for the provision of shallot marketing places called the PPB model (Onion farmer marketing). The benefits of the model are to help farmers overcome price fluctuations by delaying selling during the main harvest, where onion prices will decrease so that farmers' income is lower than expenses and help farmers shorten the marketing chain.